Respostas

2014-07-08T21:03:40-03:00
MMC = 40

4( X -5 )  +  8 ( 1 -2 X )  = 10 ( 3 - X )
------------------------------     -------------
                40                                40

4 X - 20 + 8 -16 X  = 30 - 10 X 

- 2 X  =  42     ====  multiplica por -1        ======= 2 X = -42    =====   X = -21
2014-07-08T21:10:18-03:00
(x - 5) / 10 + (1 - 2x) / 5 = (3 - x) / 4
M.M.C -> 2x - 10 + 4 - 8x / 20 = 15 - 5x / 20
               Já que temos uma igualdade podemos cortar os denominadores.
2x -10 + 4 - 8x = 15 - 5x
2x - 8x + 5x = 10 - 4 + 15
- 6x + 5x = 25 - 4
-x = 21 *(-1)
x = - 21